Living on the land: indigenous women's understanding of place - Altamirano-Jiménez, Isabel; Kermoal, Nathalie J.; Horn-Miller, Kahente (AU Press, 2016)
From a variety of methodological perspectives, contributors to Living on the Land explore the nature and scope of Indigenous women's knowledge, its rootedness in relationships, both human and spiritual, and its inseparability from land and landscape.
Le texte de Horn Miller, Kahente (2016). Distortion and Healing: Finding Balance and a ‘Good Mind’ through the rearticulation of Sky Woman’s Journey, a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; canada; cours; cree; discipline; environnement; féminisme autochtone; histoire; métis; naskapi; nicaragua; pol4105; premier cycle; ressource en ligne; régions géographiques; sciences humaines; thématiques; études autochtones; île de la tortue

Lessons in Self-Defense: Gender Violence, Racial Criminalization, and Anticarceral Feminism - Thuma, Emily (Women's Studies Quarterly, 2015)
Keywords: 1900-1999; 1980-1989; afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; féminisme autochtone; féminismes noirs; histoire; injustice; intersectionnalité; militance; patriarcat; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; résistance; sciences humaines; systèmes d'oppressions; thématiques; viol; violences; violences d'état; violences sexistes et sexuelles; états-unis; études de genres

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Section: xi, 434 pages : illustrations, cartes ; 24 cm
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail